Jägares och skogsägares syn på balansen mellan hjortvilt och skog - Nilsson, Malin (2015)
The purpose of this study is to find out more about the relation between hunters and forest owners. Do they want to know more about wild deer and forest and if they want to, how would they like to get this information. Is it both hunters and forest owners that want to learn more about forest and wild deer. What do hunters and forest owners think about feeding wild deer? To find out about this a survey was performed. The survey was done using the internet and a questionnaire was send out to 180 persons and 127 persons responded. The survey was send out to members of the Federation of Swedish Farmers, Swedish Association for Hunting and Wildlife Management and Södra. Booth hunters and forest owners want to learn more about forest and wild deer. They want to learn this through both listen, watch and perform examples. The information is maybe desired because there are many ways to practice hunting and forest owing. It was mostly the hunters who think it´s good to feed wild deer. This is maybe because they have the biggest interest in keeping the animals in there forest and a bigger population in good health.